Qualidade de vida e o impacto na adesão ao tratamento antirretroviral de pessoas que vivem com HIV - Primeira, Marcelo Ribeiro (2018)
The epidemic caused by the human immunodeficiency virus is a public health problem. One of the strategies for its control is the use of antiretroviral drugs by people infected by the virus. The viral load supression is expected when there is a early initiation of the treatment, and is linked to adherence toantiretroviral therapy. Already the quality of life of these people becomes important since living with this virus is a chronic health condition. Thereby, the assessment of quality of life in order to verify its impact on treatment adherence becomes a concern. The study aimed to assess whether quality of life is associated with adherence to antiretroviral therapy. Cross-sectional study, conducted inland of Rio Grande do Sul, Brazil. The scenario was the Outpatient Service of Infectious Diseases of Adults of the University Hospital of Santa Maria. The sample consisted of 156 adult participants who were infected with the virus and who had followed up on the service for at least three months. The data were collected from the "Questionnaire to assess the adherence to antiretroviral treatment in people with HIV/AIDS - CEAT-VIH" and "HIV/AIDS-Targeted Quality of Life Instrument (HAT-QoL)" for evaluation quality of life. The collected data were inserted on Epi Info 7.0 software, and its analyzes were performed in SPSS 21.0. Frequency analyzes were performed for the questionnaire scores, following their respective manuals. Subsequently, logistic regressions were performed to verify the associations between quality of life, compliance and biological markers of viral load and CD4 lymphocytes. Regarding the degree of compliance, 1.3% had low adherence (inadequate), 66% presented insufficient adherence and 32.7% adhered strictly (adequate). Quality of life obtained the lowest scores in the dimensions related to "Disclosure concerns" (47,40) and "Financial worries" (49,20). The dimensions with the highest scores were "Satisfaction with life" (75,52), "Sexual function" (80,69) and "Medication worries" (84,20). The "Overall function", "Medication worries" and "Provider trust" dimensions were statistically significant and positive regarding compliance, and "Disclosure concerns" presented negative statistical significance related to compliance. Moreover, it was verified that the highest quality of life scores were related to strict compliance. Finally, increased viral load is seen as detrimental to quality of life dimensions. Based on these results, it is expected that health care providers can use quality of life assessment and their influence on compliance to propose health promotion strategies for this population, intervening in the most impaired quality of life dimensions in order to prevent interference in adhesion to the antiretroviral therapy and consequently in the biological markers.